Photocuring printing ink capable of resisting electrolytic etching and adopting novel process
By using photocuring ink composed of modified epoxy resin and acrylic modified epoxy resin, combined with the synergistic effect of photoinitiator and cationic photocuring agent, the problem that ink cannot protect the integrity of the pattern line during electrolytic etching and chemical etching in the prior art is solved, and the corrosion resistance and integrity protection of ink during the etching process is achieved.
Patent Information
- Application Number
- CN202411801272.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, the dry film or circuit ink used cannot effectively protect the integrity of the pattern circuit during electrolytic etching and chemical etching, resulting in damage such as line side etching and copper exposure, resulting in poor product output.
A new process of photocuring ink is adopted, which consists of modified epoxy resin, acrylic modified epoxy resin, dipentaerythritol hexaacrylate, etc. It uses a photoinitiator and cationic photocuring agent to form a synergistic effect to improve the photocuring efficiency and quality.
The photocuring ink exhibits excellent corrosion resistance during electrolytic etching, preventing electrolyte erosion and ensuring that the ink does not fall off; it can also resist the erosion of chemical etching liquid during chemical etching modification process and protect the integrity of the pattern circuit.
Smart Images

Figure BDA0005178105610000081 
Figure BDA0005178105610000091 
Figure BDA0005178105610000092
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocurable ink preparation, and in particular relates to a photocurable ink capable of withstanding a new electrolytic etching process. Background Art
[0002] The new process of electrolytic etching to recover metals is a method of making fine circuits based on electrochemical principles, combining the two processes of electrolytic etching and metal recovery. In the process of PCB production, the unnecessary copper foil is removed by electrolytic etching technology, and the metal copper is deposited and recovered on the cathode at the same time, so as to realize the production of fine PCB circuits and the efficient and environmentally friendly recovery of metal resources, replacing the shortcomings of the traditional chemical etching process, such as the production of a large amount of waste liquid and huge processing costs. The application steps of the new process of electrolytic etching to recover metals are as follows: 1. Circuit pretreatment: remove foreign matter such as oil and rust stains on the surface of the copper plate to facilitate subsequent ink screen printing, electrolytic etching, chemical etching and other processes. 2. Screen printing ink: screen printing ink on the surface of the copper substrate, this layer of ink can protect the fine circuit in the subsequent electrolytic etching and chemical etching process. 3. Electrolytic etching and recovery of metal copper: in the electrolytic cell equipment, the copper-clad plate with the circuit pattern formed by the ink is used as the anode, and the exposed copper foil without ink coverage is dissolved by electrochemical reaction. At the same time, the copper plate is used as the cathode to deposit and recover metal copper. This process not only completes the production of fine circuits, but also realizes the recovery of metal copper. Chemical etching to remove residual copper: During the electrolytic etching process, as the copper ion concentration decreases, the corresponding electrode potential also gradually decreases. When the copper ion concentration decreases to a certain level, its electrode potential may be close to or even lower than the precipitation potential of hydrogen ions, causing hydrogen ions to begin to precipitate at the cathode, that is, hydrogen evolution reaction occurs, reducing the reduction of copper ions at the cathode, thereby affecting the complete removal of copper. Therefore, the residual copper needs to be removed by chemical etching modification.
[0003] The main difference between traditional chemical etching and electrolytic etching is that the traditional chemical etching bath solution is mainly 5% to 10% hydrochloric acid and acidic etching solution (35% CuCl2), while the electrolytic etching bath solution is mainly 10% to 15% sulfuric acid and electrolytic etching solution (CuSO4·5H2O). Traditional chemical etching removes copper by chemical dissolution, while electrolytic etching dissolves copper by electrochemical methods. At present, it is found in the actual application process that the use of dry film or circuit ink of various manufacturers after modification by electrolytic etching and chemical etching cannot well protect the integrity of the graphic circuit. The covered circuit will produce peeling and shedding of the dry film or ink, so that the product graphic circuit after etching has serious side corrosion, copper exposure and other damage phenomena, resulting in the output of defective products.
[0004] Therefore, it is an urgent problem to develop a photocurable ink that can withstand the new electrolytic etching process to meet the PCB industry's demand for a new electrolytic etching process for metal recovery. Summary of the invention
[0005] The object of the present invention is to provide a photocurable ink that can withstand a new electrolytic etching process, so as to solve one of the technical problems mentioned in the background technology.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A photocurable ink resistant to a new electrolytic etching process, comprising the following raw materials in parts by weight:
[0008] Modified epoxy resin UV-1 40-60 parts, acrylic modified epoxy resin UV-2 40-60 parts, dipentaerythritol hexaacrylate 15-25 parts, pentaerythritol tetraacrylate 10-20 parts, trimethylolpropane triacrylate 5-10 parts, trifunctional acid ester 0.5-1 parts, tripropylene glycol diacrylate 10-15 parts, γ-methacryloxypropyl trimethoxysilane 0.1-0.2 parts, 3-(2,3-epoxypropoxy)propyl trimethoxysilane 0.1-0.2 parts, 2-ethyl anthraquinone 1-5 parts, photoinitiator 6511-5 parts, photoinitiator TPO 2-3 parts, cationic light curing agent UVI-6976 0.1-0.3 parts, cationic light curing agent UVI-6992 0.1-0.3 parts, talc 30-40 parts, barium sulfate 20-25 parts, calcium magnesium carbonate 15-20, fumed silica 3-5 parts, titanium cyanine blue 0.8-1.0 parts, defoaming agent 0.2-0.5 parts, polyether siloxane copolymer (wetting and leveling agent) 0.2-0.5 parts.
[0009] Furthermore, the preparation steps of the modified epoxy resin UV-1 are as follows:
[0010] Step 1, adding o-cresol epoxy resin and acrylic acid according to the equivalent ratio into a four-necked flask, filling with dry air, heating to 100° C., observing that the o-cresol epoxy resin is in liquid state, adding acrylic acid, adding antioxidant, triphenylphosphine and polymerization inhibitor according to the total weight of the o-cresol epoxy resin and acrylic acid, heating to 125-130° C. for reaction for 3-5 hours, and determining that the acid value is less than 3.0 to obtain a modified o-cresol epoxy acrylate copolymer;
[0011] Step 2, maintaining the modified o-cresol-formaldehyde epoxy acrylate copolymer at 100° C., adding IPDI and MDI-50 according to the equivalent ratio of the o-cresol-formaldehyde epoxy acrylate copolymer, IPDI and MDI-50, maintaining the temperature at 100° C. for 2 to 3 hours, and determining that NCO% is less than 0.2 to obtain a modified multifunctional o-cresol-formaldehyde epoxy polyurethane acrylate copolymer;
[0012] Step 3, according to the weight ratio, the modified multifunctional o-cresol epoxy polyurethane acrylate, the alicyclic epoxy resin and the bisphenol A epoxy resin are put into a four-necked flask and maintained at 100° C. The alicyclic epoxy resin and the bisphenol A epoxy resin are put into the four-necked flask in sections to carry out a sequential IPN structure (Sequential IPN) preparation process. After the addition is completed, the viscosity is tested every 1 hour. When there is no change in the two viscosity measurements, the modified epoxy resin UV-1 is obtained.
[0013] Furthermore, in step 1, the equivalent ratio of the o-cresol-formaldehyde epoxy resin to the acrylic acid is 1:(0.8-1.2).
[0014] Furthermore, in step 1, the amount of the antioxidant is 0.5% to 2.0% of the total weight of the o-cresol epoxy resin and the acrylic acid; the amount of triphenylphosphine is 0.5% to 2.0% of the total weight of the o-cresol epoxy resin and the acrylic acid; and the amount of the inhibitor is 500 to 1000 ppm of the total weight of the o-cresol epoxy resin and the acrylic acid.
[0015] Furthermore, in step 2, the equivalent ratio of the modified o-cresol-formaldehyde epoxy acrylate copolymer, IPDI and MDI-50 is 1:(0.2-0.4):(0.1-0.3).
[0016] Furthermore, in step 3, the weight ratio of the modified multifunctional o-cresol epoxy polyurethane acrylate, alicyclic epoxy resin and bisphenol A epoxy resin is (40:30:30) to (90:5:5).
[0017] Furthermore, the raw materials of the acrylic modified epoxy resin UV-2 include modified epoxy resin UV-1, hydroxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, o-cresol epoxy resin, antioxidant and inhibitor; wherein the weight ratio of hydroxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride and o-cresol epoxy resin is 60-70:70-75:90-95:30-35:33-37:100-150.
[0018] Furthermore, the ratio of the added amount of the modified epoxy resin to the total weight of hydroxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride and o-cresol-formaldehyde epoxy resin is (5:5) to (7:3).
[0019] Furthermore, the added amount of the antioxidant is 0.5% to 2% of the total weight of the acrylic modified epoxy resin UV-2 raw material; the added amount of the inhibitor is 500 to 1000 ppm of the total weight of the acrylic modified epoxy resin UV-2 raw material.
[0020] Furthermore, the preparation steps of the acrylic modified epoxy resin UV-2 are as follows:
[0021] The modified epoxy resin UV-1 is put into a four-necked flask according to weight parts, and the flask is filled with dry air. Hydroxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride are added according to weight parts, and an antioxidant and a polymerization inhibitor are added according to the total weight of the above raw materials. The temperature is raised to 100-120° C. and the reaction is carried out for 2-3 hours to carry out a ring-opening reaction. The reaction temperature is 120-130° C. and the reaction time is 3-5 hours. After the acid value is measured twice and remains unchanged, the acrylic modified epoxy resin UV-2 is obtained.
[0022] In the above technical scheme, the monomer polymers used are composed of dipentaerythritol hexaacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, trifunctional acid ester, tripropylene glycol diacrylate, γ-methacryloxypropyltrimethoxysilane and 3-(2,3-epoxypropoxy)propyltrimethoxysilane. The bulk viscosity of the above monomer polymers is low, which can effectively adjust the viscosity of the ink and avoid serious problems such as loss of ink adhesion and ink embrittlement due to excessive monomer amount.
[0023] In the above technical scheme, the photoinitiator used is composed of 2-ethylanthraquinone, photoinitiator 651, photoinitiator TPO, cationic photocuring agent UVI-6976 and cationic photocuring agent UVI-6992. The embodiment uses a photoinitiator and a cationic photocuring agent in combination, the purpose of which is to produce a synergistic effect and improve the efficiency and quality of photocuring. The free radical photoinitiator can quickly generate free radicals and promote free radical polymerization reactions; while the cationic photocuring agent can generate super strong proton acid to initiate cationic polymerization reactions. The combination of the two can simultaneously cause free radical polymerization and cationic polymerization, thereby accelerating the curing process, improving the curing efficiency and the ink bridging density, and then improving its corrosion resistance, mechanical properties, and physical and chemical properties.
[0024] In the above technical solution, the fillers used are composed of talcum powder, barium sulfate, calcium magnesium carbonate and fumed silica. The above fillers can effectively improve the key properties of ink such as aging resistance, color development, hiding power, thixotropy and glossiness.
[0025] In the above technical solution, the additives used are composed of phthalocyanine blue, defoamer, and polyether siloxane copolymer. Phthalocyanine blue is a dyeing raw material that can effectively provide visual effects and recognition; defoamer and polyether siloxane copolymer (leveling wetting agent) can effectively adjust the suitability of ink for screen printing.
[0026] Beneficial effects of the present invention:
[0027] The photocurable ink provided in the present invention can exhibit excellent corrosion resistance during electrolytic etching, effectively preventing the electrolyte from corroding the ink, and ensuring that the ink remains intact, does not fall off, and does not dissolve during the etching process. This property enables the ink to play a key role in the process of electrolytic etching to recover metals, protecting the patterns and lines in the non-etched areas, and at the same time resisting the corrosion of the chemical etching solution during the chemical etching modification process.
[0028] The photocurable ink provided in the present invention can be firmly attached to the surface of metal or other substrates after curing, and is not easy to peel off or crack. This high adhesion ensures the stability of the ink during the electrolytic etching process, as well as the reliability in subsequent processing and use. The cured ink has high hardness, wear resistance and toughness, can withstand certain mechanical stress and impact, and protect the substrate surface from damage.
[0029] The photocurable ink provided in the present invention does not require the addition of solvents during production and use, and thus does not generate harmful substances such as volatile organic compounds (VOCs), thus meeting environmental protection requirements.
[0030] The invention can be rapidly cured by ultraviolet or visible light irradiation, and does not require high-energy-consuming steps such as high-temperature drying, thereby saving energy and time.
[0031] The light-curable ink provided in the present invention can be rapidly cured under ultraviolet or visible light irradiation, and the curing process can usually be completed within a few seconds to a few minutes. This rapid curing feature greatly improves production efficiency and shortens production cycle.
[0032] The curing process of the light-curable ink provided in the present invention is relatively stable and not easily affected by external environmental factors, thus ensuring the stability and repeatability of the process. In addition, by adjusting the formulation and curing conditions (such as light intensity, time, etc.) of the light-curable ink, precise control of the curing process and the performance of the cured product can be achieved to meet the needs of different application scenarios.
[0033] In summary, the photocurable ink provided by the present invention that can withstand the new electrolytic etching process has excellent technical effects in terms of excellent corrosion resistance, good adhesion and mechanical properties, solvent-free, energy-saving and high efficiency, curing speed, stability and controllability. These characteristics make the ink have a wide range of application prospects and important application value in the process of electrolytic etching to recover metals. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment provides a modified epoxy resin UV-1, and the preparation steps are as follows:
[0037] Step 1, o-cresol epoxy resin (purchased from Shengquan, epoxy equivalent of 200-215) and acrylic acid (purchased from Shanghai Yongzheng) according to the equivalent ratio of 1:0.8, the o-cresol epoxy resin is put into a four-necked flask, filled with dry air, heated to 100 ° C, observed that the o-cresol epoxy resin is in liquid state, and acrylic acid is added. According to the total weight of the o-cresol epoxy resin and acrylic acid, 0.5% of antioxidant (BHT, purchased from Jiangsu Ningkang), 0.5% of triphenylphosphine (TPH, purchased from Suzhou Jinyuan) and 500ppm of polymerization inhibitor (MEHQ, purchased from Changzhou Shuojin) are added, the temperature is raised to 125 ° C for reaction for 3 hours, and the acid value is measured to be <3.0 to obtain a modified o-cresol epoxy acrylate copolymer;
[0038] Step 2, maintaining the modified o-cresol novolac epoxy acrylate copolymer at 100° C., adding IPDI and MDI-50 (purchased from Yantai Wanhua) according to the equivalent ratio of o-cresol novolac epoxy acrylate copolymer, IPDI (purchased from Yantai Wanhua) to MDI-50 (purchased from Yantai Wanhua) of 1:0.2:0.1, maintaining the reaction at 100° C. for 2 hours, and determining that NCO% is less than 0.2 to obtain a modified multifunctional o-cresol novolac epoxy polyurethane acrylate copolymer;
[0039] Step 3, the modified multifunctional o-cresol epoxy polyurethane acrylate, alicyclic epoxy resin and bisphenol A epoxy resin are added into a four-necked flask according to a suitable weight ratio of 40:30:30 and maintained at 100°C, and the alicyclic epoxy resin and bisphenol A epoxy resin are added into the four-necked flask in sections to carry out a sequential IPN structure (Sequential IPN) preparation process. After the addition is completed, the viscosity is tested every 1 hour. When there is no change in the two viscosity measurements, the modified epoxy resin UV-1 is obtained.
[0040] Example 2
[0041] The present embodiment provides an acrylic modified epoxy resin UV-2, the raw materials of the acrylic modified epoxy resin UV-2 include modified epoxy resin UV-1, 60 parts of hydroxyethyl methacrylate (purchased from Anhui Lianhua), 70 parts of hydroxypropyl methacrylate (purchased from Anhui Lianhua), 90 parts of tetrahydrophthalic anhydride (purchased from Jiangsu Haolong), 30 parts of methyltetrahydrophthalic anhydride (purchased from Tiancheng Chemical), 33 parts of methylhexahydrophthalic anhydride (purchased from Jiangsu Taitel), 100 parts of o-cresol epoxy resin (purchased from Shengquan, epoxy equivalent 200-215), antioxidant (BHT) and inhibitor (MEHQ).
[0042] The ratio of the added amount of the modified epoxy resin to the total weight of hydroxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride and o-cresol-formaldehyde epoxy resin is 5:5;
[0043] The added amount of the antioxidant is 0.5% of the total weight of the acrylic acid modified epoxy resin UV-2 raw material; and the added amount of the inhibitor is 500ppm of the total weight of the acrylic acid modified epoxy resin UV-2 raw material.
[0044] The specific preparation steps of the acrylic modified epoxy resin UV-2 are as follows:
[0045] The modified epoxy resin UV-1 is put into a four-necked flask by weight, and the flask is filled with dry air. Hydroxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride are added by weight, and an antioxidant (BHT) and a polymerization inhibitor (MEHQ) are added according to the total weight of the above raw materials. The temperature is raised to 100° C. and reacted for 2 hours to carry out a ring-opening reaction. Subsequently, o-cresol-formaldehyde epoxy resin is added to react with the other end carboxyl group of tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, and methylhexahydrophthalic anhydride after ring opening. The reaction temperature is 120° C. and the reaction time is 3 hours. After the acid value is measured twice and remains unchanged, acrylic modified epoxy resin UV-2 is obtained.
[0046] Example 3
[0047] This embodiment provides a photocurable ink that can withstand a new electrolytic etching process. The specific raw materials and usage weight parts are shown in Table 2.
[0048] Example 4
[0049] This embodiment provides a photocurable ink that can withstand a new electrolytic etching process. The specific raw materials and usage weight parts are shown in Table 2.
[0050] Example 5
[0051] This embodiment provides a photocurable ink that can withstand a new electrolytic etching process. The specific raw materials and usage weight parts are shown in Table 2.
[0052] Comparative Example 1
[0053] This comparative example provides a photocurable ink that can withstand a new electrolytic etching process. The specific raw materials and usage weight parts are shown in Table 2.
[0054] Comparative Example 2
[0055] This comparative example provides a photocurable ink that can withstand a new electrolytic etching process. The specific raw materials and usage weight parts are shown in Table 2.
[0056] 1. The sources of raw materials used in the photocurable ink of the new electrolytic etching resistant process in Examples 3-5 and Comparative Examples 1-2 are shown in Table 1:
[0057] Table 1
[0058]
[0059]
[0060] 2. The specific raw materials and weight proportions of the photocurable ink resistant to electrolytic etching in Examples 3-5 and Comparative Examples 1-2 are shown in Table 2.
[0061] Table 2
[0062]
[0063]
[0064]
[0065] 3. The performance of the photocurable ink obtained in Examples 3 to 5 and Comparative Examples 1 to 2 that can resist electrolytic etching was tested. Test method: ink was screen printed onto a copper foil substrate. UV curing energy: 900-1300 mJ / cm 2 , the test results are shown in Table 3:
[0066] Table 3
[0067]
[0068] From the data in Table 2-3, it can be seen that the photocurable ink provided by the present invention is resistant to the new electrolytic etching process, has a fast photocuring speed, and the ink after curing into a film has good adhesion to the copper foil substrate, and has the effects of complete electrolytic etching resistance, no ink shedding and peeling, good chemical etching resistance, and the ink can be completely removed by alkali retreatment.
[0069] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A photocurable ink that can withstand a new electrolytic etching process, characterized in that: It includes the following raw materials in parts by weight: Modified epoxy resin UV-1 40-60 parts, acrylic modified epoxy resin UV-2 40-60 parts, dipentaerythritol hexaacrylate 15-25 parts, pentaerythritol tetraacrylate 10-20 parts, trimethylolpropane triacrylate 5-10 parts, trifunctional acid ester 0.5-1 parts, tripropylene glycol diacrylate 10-15 parts, γ-methacryloxypropyl trimethoxysilane 0.1-0.2 parts, 3-(2,3-epoxypropoxy)propyl trimethoxysilane 0.1-0.2 parts, 2-ethyl anthraquinone 1-5 parts, photoinitiator 6511-5 parts, photoinitiator TPO 2-3 parts, cationic light curing agent UVI-6976 0.1-0.3 parts, cationic light curing agent UVI-6992 0.1-0.3 parts, talc powder 30-40 parts, barium sulfate 20-25 parts, calcium magnesium carbonate 15-20, fumed silica 3-5 parts, titanium cyanine blue 0.8-1.0 parts, defoaming agent 0.2-0.5 parts, polyether siloxane copolymer 0.2-0.5 parts.
2. The photocurable ink resistant to electrolytic etching according to claim 1, characterized in that: The preparation steps of the modified epoxy resin UV-1 are as follows: Step 1, adding o-cresol epoxy resin and acrylic acid according to the equivalent ratio into a four-necked flask, filling with dry air, heating to 100° C., observing that the o-cresol epoxy resin is in liquid state, adding acrylic acid, adding antioxidant, triphenylphosphine and polymerization inhibitor according to the total weight of the o-cresol epoxy resin and acrylic acid, heating to 125-130° C. for reaction for 3-5 hours, and determining that the acid value is less than 3.0 to obtain a modified o-cresol epoxy acrylate copolymer; Step 2, maintaining the modified o-cresol-formaldehyde epoxy acrylate copolymer at 100° C., adding IPDI and MDI-50 according to the equivalent ratio of the o-cresol-formaldehyde epoxy acrylate copolymer, IPDI and MDI-50, maintaining the temperature at 100° C. for 2 to 3 hours, and determining that NCO% is less than 0.2 to obtain a modified multifunctional o-cresol-formaldehyde epoxy polyurethane acrylate copolymer; Step 3, according to the weight ratio, the modified multifunctional o-cresol epoxy polyurethane acrylate, alicyclic epoxy resin and bisphenol A epoxy resin are put into a four-necked flask and maintained at 100°C, and the alicyclic epoxy resin and bisphenol A epoxy resin are put into the four-necked flask in sections to carry out a step-by-step IPN structure preparation process. After the addition is completed, the viscosity is tested every 1 hour. When there is no change in the two viscosity measurements, the modified epoxy resin UV-1 is obtained.
3. The photocurable ink resistant to electrolytic etching according to claim 2, characterized in that: In step 1, the equivalent ratio of o-cresol epoxy resin to acrylic acid is 1:(0.8-1.2).
4. The photocurable ink resistant to electrolytic etching according to claim 2, characterized in that: In step 1, the amount of the antioxidant is 0.5% to 2.0% of the total weight of the o-cresol epoxy resin and the acrylic acid; the amount of the triphenylphosphine is 0.5% to 2.0% of the total weight of the o-cresol epoxy resin and the acrylic acid; and the amount of the inhibitor is 500 to 1000 ppm of the total weight of the o-cresol epoxy resin and the acrylic acid.
5. The photocurable ink resistant to electrolytic etching according to claim 2, characterized in that: In step 2, the equivalent ratio of the modified o-cresol-formaldehyde epoxy acrylate copolymer, IPDI and MDI-50 is 1:(0.2-0.4):(0.1-0.3).
6. The photocurable ink resistant to electrolytic etching according to claim 2, characterized in that: In step 3, the weight ratio of the modified multifunctional o-cresol epoxy polyurethane acrylate, alicyclic epoxy resin and bisphenol A epoxy resin is (40:30:30) to (90:5:5).
7. The photocurable ink resistant to electrolytic etching according to claim 1, characterized in that: The raw materials of the acrylic modified epoxy resin UV-2 include modified epoxy resin UV-1, hydroxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, o-cresol epoxy resin, antioxidant and polymerization inhibitor; wherein the weight ratio of hydroxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride and o-cresol epoxy resin is 60-70:70-75:90-95:30-35:33-37:100-150.
8. The photocurable ink resistant to electrolytic etching according to claim 7, characterized in that: The ratio of the added amount of the modified epoxy resin to the total weight of hydroxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride and o-cresol epoxy resin is (5:5) to (7:3).
9. The photocurable ink resistant to electrolytic etching according to claim 7, characterized in that: The added amount of the antioxidant is 0.5% to 2% of the total weight of the acrylic acid modified epoxy resin UV-2 raw material; the added amount of the polymerization inhibitor is 500 to 1000ppm of the total weight of the acrylic acid modified epoxy resin UV-2 raw material.
10. The photocurable ink resistant to electrolytic etching according to claim 7, characterized in that: The preparation steps of the acrylic acid modified epoxy resin UV-2 are as follows: The modified epoxy resin UV-1 is put into a four-necked flask according to weight parts, and the flask is filled with dry air. Hydroxyethyl methacrylate, hydroxypropyl methacrylate, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride are added according to weight parts, and an antioxidant and a polymerization inhibitor are added according to the total weight of the above raw materials. The temperature is raised to 100-120° C. and the reaction is carried out for 2-3 hours to carry out a ring-opening reaction. The reaction temperature is 120-130° C. and the reaction time is 3-5 hours. After the acid value is measured twice and remains unchanged, the acrylic modified epoxy resin UV-2 is obtained.